Quercetin Increases MUC2 and MUC5AC Gene Expression and Secretion in Intestinal Goblet Cell-Like LS174T via PLC/PKCα/ERK1-2 Pathway - Damiano, Simona; Sasso, Anna; De Felice, Bruna; Di Gregorio, Ilaria; La Rosa, Giuliana; Lupoli, Gelsi A.; Belfiore, Anna; Mondola, Paolo; Santillo, Mariarosaria (Frontiers in Physiology, 2018)
The main dietary flavonoid quercetin, is known to preserve the integrity of gastrointestinal barrier and to have anti-inflammatory, anti-cancer, anti-fibrotic and other beneficial properties. Many of the biological effects of quercetin appear to be associated to the modulation of cell signaling pathways, rather than to its antioxidant activity. In spite of the large number of data available on the molecular and cellular mechanisms by which quercetin exerts its biological effects, including protection of intestinal barrier function, there is a lack of data about the role of this substance on the expression and/or the secretion of mucins released by intestinal goblet cells. Here we investigated the effects of quercetin on the secretion and the gene expression of the main intestinal gel-forming mucins, MUC2 and MUC5AC, and the signaling mechanisms underlined, in human intestinal goblet cell-like LS174T. We found that quercetin increases intracellular Ca2+ levels and induces MUC2 and MUC5AC secretion in a Ca2+-dependent manner. Quercetin also induces mRNA levels of both secretory mucins. Quercetin stimulation of LS174T cells increases phosphorylation levels of extracellular signal regulated kinase (ERK)1-2 and protein kinase C (PKC) α and the induction of MUC2 and MUC5AC secretion and mRNA relies on phospholipase C (PLC), PKC and ERK1-2 signaling pathways since the PLC inhibitor U73122, the PKC inhibitor bisindolylmaleimide (BIM) and the ERK1-2 pathway inhibitor PD98059, all revert the stimulatory effects of quercetin. We also demonstrated that the induction of mucin gene expression by quercetin is not limited to goblet cells. Indeed, quercetin induces mRNA levels of MUC2 and MUC5AC via PKCα/ERK1-2 pathway also in the human intestinal epithelial Caco-2 cells. These data highlight a novel mechanism thereby quercetin, regulating the secretory function of intestinal goblet cells and mucin levels in enterocytes may exert its protective effects on intestinal mucosal barrier.